Two dates from Vladimir Golenishchev’s biography - Ivan Ladynin (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi)
The article is intended to refine the dates of two important episodes in the biography of the outstanding Russian Egyptologist Vladimir Golenishchev (1856-1947), the collector of antiquities that laid the cornerstone for the Egyptian department of the Pushkin State Museum of Fine Arts, Moscow. Russian Egyptologists were sure that Golenishchev acquired the first object of his collection at the age of 14; this came to be known from the Soviet Egyptologist and Orientalist Vassiliy Struve, who had once heard it from Golenishchev himself. However, the file-cabinet of Golenishchev’s collection preserves a card for the ushebti of Qeref-en-Ptah bearing a mark that this was the first object that Golenishchev possessed given to him by the ambassador of Greece at St. Petersburg Dimitrios Buduris. As the diplomat started his mission at St. Petersburg in August 1871, he could not make this present before Golenishchev was at least 15 years old. There is also an uncertainty about the time of Golenishchev’s purchasing three important papyri: The Travel of Wenamun to Byblos, the Golenishchev Onomasticon and a literary letter (Pushkin Museum 1,1b 127). Golenishchev dated this purchase to the autumn of 1891 in his publications of 1897 and 1899, but the unpublished account of his travel to Egypt in 1890-1891 (now at the Archives of Vladimir Golenishchev at Paris) makes it perfectly clear that this took place in November and December of 1890. Symptomatically both false dates go back to Golenishchev’s statements. While the former one could be due to a real failure of memory or to the desire to bring the start of his collection closer to his childhood, the latter can be explained by an urge to disguise somehow the circumstances of his purchase by falsifying its date.